The prognostic value of baseline CD4R cell count beyond 6 months of antiretroviral therapy in HIV-positive patients in a resource-limited setting - Mills, Edward J.; Bakanda, Celestin; Birungi, Josephine; Yaya, Sanni; Ford, Nathan (Aids, 2012)
The risk of death is highest in the first few months after initiation of antiretroviral therapy (ART). We examined whether initial CD4þ cell count maintains a strong prognostic value among patients with at least 6 months follow-up after the initiation of ART. Design: Observational study of HIV patients in Uganda aged 14 years or older enrolled in 10 clinics across Uganda. Methods: Baseline CD4þ cell count of patients with more than 6 months of follow-up were stratified into categories (<50, 50–99, 100–149, 150–249, >250 cells/ml). A Kaplan–Meier survival analysis and Cox proportional hazards regression was used to model the associations between baseline CD4þ cell count and mortality. Results: Of 22 315 patients, 20 730 (92.8%) had more than 6 months of follow-up. Six hundred and eleven (2.9%) patients died during follow-up and 737 (3.6%) were lost to follow-up. Relative to a baseline CD4þ cell counts of less than 50 cells/ml, the adjusted hazard ratios for death were 0.83 [95% confidence interval (CI) 0.67–1.02], 0.71 (95% CI 0.57–0.88), 0.52 (95% CI 0.42–0.64), and 0.55 (95% CI 0.42–0.70) favouring those with baseline CD4þ cell counts of 50–99, 100–149, 150–249, and at least 250 cells/ml, respectively. Differing ages and male sex increased the likelihood of mortality. Conclusion: Among patients with more than 6 months of follow-up after initiation of ART, baseline CD4þ cell count at initiation still has important prognostic value. This suggests that active engagement and earlier treatment initiation is important for longterm survival.
Keywords: Antiretroviral therapy; CD4þ; HIV; Prognosis; Uganda; Sub-Saharan Africa